Client Tribute Plan and Patient Satisfaction in Shiraz Hospitals - Ali Keshtkaran; Vahid Taft; Vida Keshtkaran; Alireza Heidari; Javad Shahmohammadi; Maryam Dehbozorgi; Mansoureh Lotfi (Tehran University of Medical Sciences, 2017)
Background and Aim: The patient is the main customer for hospital services. Patient satisfaction can reflect if the services are performed correctly. The aim of this study was to determine the relationship between the degree of client tribute plan and inpatients and outpatients satisfaction in Shiraz hospitals. Materials and Methods: This descriptive-analytic and cross sectional study was done among 211 inpatients and 1,175 outpatients in 8 Shiraz hospitals. The instruments for data collection were two client tribute plan and patient satisfaction questionnaires. Data collected by interviews and observation. Data were entered into SPSS. Descriptive statistics and Pearson correlation test were used for data analysis. Results: Forty five point four percent of patients and 44.1 percent of outpatients assessed the hospital service satisfaction as weak. The mean score of inpatient and outpatient satisfaction was 60.53±8.9 and 54.22±12.6 respectively. There were significant relationship between type of admission and satisfaction (p=0.001). Mean score of client tribute plan was 182.44±11.8 that placed in the appropriate level. There were no significant relationships between client tribute plan and inpatients and outpatients satisfaction (p=0.143). Conclusion: Although client tribute plans perform properly, patient satisfaction is low. In this regard, it is recommended that review client tribute plan clients in healthcare systems and adopt its contents with the needs of patients.